Improving undergraduate students' positive affect through mindful art therapy - Ha, Ming Hui; Ma'rof, Aini Marina (Human Resource Management Academic Research Society, 2019)
With the increasing popularity of positive psychology, current studies are more concerned in promoting mental health rather than only focusing on pathological disorders. Hence, the term “subjective well-being” was introduced as a pertinent area of study where new research has emerged regarding its components: positive affect, negative affect and life satisfaction. The current study serves as a preliminary study within the Malaysian higher education context with the aim to examine the impact of a relatively new approach to mindful art therapy, Zentangle®, on improving the subjective well-being of first year teacher trainee students in a Malaysian public university in terms of positive affect. This study adopted the one-group pretest posttest design in which 44 students participated in the study. Participants were required to answer two sets of questionnaires before and after the Zentangle® intervention. Through descriptive and inferential analyses of data obtained, this study found that the level of positive affect was not significantly correlated with stress level. In addition, the most important finding in this study was level of subjective well-being in terms of positive affect significantly increased after participants’ experience with mindful art therapy. This study serves as the first, or one of the first to study on Zentangle® in the Malaysian context and aims to provide insights on mindful art therapy and positive affect, probing future studies looking into related topics.